Hepatic infection by thymidine kinase-positive and thymidine kinase-negative herpes simplex virus after partial hepatectomy. - Fang, Z Y (1983)
Herpes simplex virus (HSV) infection of mouse liver after partial hepatectomy was studied. Partial hepatectomy resulted in the rapid onset of cellular DNA synthesis and the appearance of many mitotic figures (peak, 3 days after surgery). Similar changes were not seen in control animals. After partial hepatectomy, the mice were infected with thymidine kinase-positive (TK+) and -negative (TK-) HSV to investigate virus titers in liver tissue during liver cell replication. In control unoperated mice, liver titers of TK+ HSV (2 X 10(3) PFU/g) were greater than those of mice inoculated with TK HSV (4 X 10(1) to 5 X 10(2) PFU/g). After partial hepatectomy, TK+ and TK- HSV titers increased, and peak TK+ and TK- HSV titers were similar (6 X 10(5) to 8 X 10(5) PFU/g). Hepatic infection was further investigated by infectious center (IC) assays. The numbers of ICs for TK+ HSV increased 50-fold after partial hepatectomy, whereas the increase was less for TK- HSV. From the results of these studies, we hypothesize that the increase in hepatic TK+ HSV after hepatectomy may have been largely due to the increase in ICs, whereas the increase in hepatic TK- HSV was due, in part, to the increase in ICs, but may also have been due to the enhanced synthesis of TK- HSV in replicating liver cells.